Предмет: Алгебра,
автор: LenaOk11
плииз (х-y)(x+y)-(a-x+y)(a-x-y)-a (2x-a)=0
Ответы
Автор ответа:
0
(x-y)(x+y)-(a-x+y)(a-x-y)-a(2x-a)=0
x^2-y^2-(a^2-ax-ay-ax+x^2+xy+ay-xy-y^2)-2ax+a^2=0
x^2-y^2-a^2+2ax-x^2+y^2-2ax+a^2=0
0=0
левая часть = правой части для любых х,у и а
что и требовалось доказать
Похожие вопросы
Предмет: Другие предметы,
автор: yyayyayayyaaay
Предмет: Математика,
автор: loh0550
Предмет: Физика,
автор: seksafon655
Предмет: Физика,
автор: dimon199696
Предмет: Математика,
автор: moldirsarsekova